The Influence of Motivation, Work Discipiline, and Work Environment on Employee Performance in Waste Management at DLHKP Kediri City - sholikhah, azizatus; Hadi S, Dodi Kusuma (Universitas Nusantara PGRI Kediri, 2025)
Research objectives: This study looks at how employee performance in trash management at DLHKP Kediri City is affected by motivation, work ethics, and workplace conditions.Design/Method/Approach: Employees of DLHKP Kota Kediri were given questionnaires to gather data for the quantitative analysis. Various tests, including validity and reliability assessments, were conducted, followed by data analysis using multiple linear regression, t-tests, and F-tests in SPSS version 25.0. Additionally, classical assumption tests were applied to enhance the reliability of the study’s findings.The results of the study show: Based on the coefficient of determination (R2), the three factors which include social work environment, employee discipline, and motivation can affect employee results significantly and earning contribute 2% of the whole variation in employee output.Theoretical contribution/originality: This study lends credence to the idea that the work environment, employee discipline, and motivate trigger all have more impact on boosting performance. The concurrent analysis of this study provides a novel viewpoint on the factors that influence performance in the waste management sector.Practice/Policy Implications: To improve overall performance, this study suggests that DLHKP Kota Kediri focus more on elements that can improve worker performance, such as offering appropriate incentives, strengthening work discipline, and building a more favorable work environment.Research limitations: This research is limited to the waste management sector in DLHKP Kediri City and only covers a few variables that affect employee performance. Future research suggests expanding the scope to other sectors and incorporating additional relevant variables to improve employee performance in the public sector.